Musik an den schwäbischen Zollernhöfen der Renaissance. Beiträge zur Kulturgeschichte des Deutschen Südwestens. - Schmid, Ernst Fritz 1904-1960 (Kassel Bärenreiter, 1962)
Erstes Buch: Sigmaringen und Haigerloch - Zweites Buch: Hechingen
The members of the House of Hohenzollern, who are historically linked to the County of Zollern with Hohenzollern Castle near Hechingen in present-day Baden-Württemberg and who once did not leave the Swabian ancestral lands, are categorised as the Swabian Hohenzollerns. Burchardus and Wezil were first mentioned by a monk in a chronicle in 1061. In 1576, the two counties of Hohenzollern-Hechingen and Hohenzollern-Sigmaringen were created, from which the principalities of Hohenzollern-Hechingen and Hohenzollern-Sigmaringen were formed in 1623. Only the Hohenzollern-Sigmaringen line still exists today.
Herausgegeben im Auftrag Sr. Kgl. Hoheit Fürsten Friedrich von Hohenzollern
Keywords: House of Hohenzollern; Schloss Haigerloch (Baden-Württemberg, Germany); Schloss Sigmaringen (Baden-Württemberg, Germany); 15th Century (1401-1500); 16th Century (1501-1600); 17th Century (1601-1700); Renaissance (1400-1600); Music history; Court; Cappella; Musician; Nobility; Patronage; Swabia (= Schwaben, Germany); Baden-Württemberg (Germany)